The social media whatsapp to support physics learning problem solving on online tutorial activities in distance education - Widiasih Widiasih; A Permanasari; Riandi Riandi; T Damayanti (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
One of the subjects that must be taken by distance education students of Physics of Universitas Terbuka (UT) is PEFI4201 Physics Learning Strategy. The average score obtained by students in PEFI4201 courses is low. To master the concept of this course students are given learning assistance services in the form of online tutorial (tuton) in addition to studying the module as the main teaching material. However, the students' activity in the tuton is less encouraging. Thus the social media WhatsApp (WA) is required to enable students to follow the tutons. The purpose of this research is to describe WA communication process in support of tutons implementation. The method used in this research is descriptive qualitative and quantitative to analyze WA communication process in support of tutons implementation. The results of this study obtained that WA strongly supports student activeness in tutons. Communication occurring from 28 August to 29 October 2017 consists of academic administration 6.67%; reminder 22.42%; explanation of material 62,42%; and technical explanation elearning 8.48%.Two-way communication can work well through WA, because WA is more familiar to be accessed anywhere, anytime. If the student is late to access every step of the weekly learning activity on the tutons, be reminded through WA. Progress of individual progress in completing discussions and tuton assignments informed through WA with the intent to motivate students to immediately follow the discussion and complete the tuton task. Thus it can be concluded that social media WA can support tuton activities.